Pemahaman Aplikasi E-Bekal bagi Wali Asuh Santri sebagai Upaya Pencegahan Penyalahgunaan Uang Belanja Santri di Pesantren - Nadiyah Nadiyah; M Syafiih; Deviana Dianita; Musrifatul Arifah; Murliatus Saniyah; Siti Qurrotul Fu’adi; Titin Agustin; Virda Virdausih Putri; Nurul Hidayati (Universitas Nurul Jadid, 2021)
E_BEKAL is a shopping application for students at the Nurul Jadid Paiton Probolinggo Islamic Boarding School, the idea of making the application is to provide solutions to problems experienced by the Islamic boarding school. These problems include (1) the santri's spending money is not controlled by the management, there is an imbalance in the santri's spending money coming from an economy that is capable of spending a lot of spending. Conditions like this will create social jealousy for other santri, the management immediately responds to this condition because some observations and evaluation results from the results of cases that occur there are some santris who will be affected by the lifestyle of students whose economies are related to students with weak economies; (2) there are frequent cases of losing money in provisions for santri. Based on the results of the evaluation of the management every month, cases of losing money from santri can occur every day; (3) can regulate santri spending money with pesantren policies; (4) parents can control and evaluate santri spending money, santri guardians can also TOPUP (send) money online using an application according to the bank specified by the pesantren; and (5) Pesantren administrators conduct socialization and training on the use of the E_BEKAL application as provisions for students' understanding of the use of the E_BEKAL application.Keywords: Boarding School, Application, Management, Provision, Shopping